2011
DOI: 10.1161/circep.110.959957
|View full text |Cite
|
Sign up to set email alerts
|

Endocardial Unipolar Voltage Mapping to Detect Epicardial Ventricular Tachycardia Substrate in Patients With Nonischemic Left Ventricular Cardiomyopathy

Abstract: Background-Patients with nonischemic left ventricular cardiomyopathy (LVCM) and ventricular tachycardia (VT) havecomplex 3-dimensional substrate with variable involvement of the endocardium (ENDO) and epicardium (EPI). The purpose of this study was to determine whether ENDO unipolar (UNI) mapping with a larger electric field of view could identify EPI low bipolar (BIP) voltage regions in patients with LVCM undergoing VT ablation. Methods and Results-The reference value for normal ENDO unipolar voltage was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
224
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 358 publications
(230 citation statements)
references
References 16 publications
3
224
1
2
Order By: Relevance
“…The hypothesis was that endocardial areas of scar may show low bipolar voltage but near‐normal unipolar voltage. Unipolar voltage maps include the far‐field electrical activity from the overlying viable myocardium and hence can differentiate thin endocardial scars from thick transmural scars 16, 17. In this study, in the three dogs with large confluent infarcts, endocardial scar areas showed high unipolar voltage (>15 mV) and transmural scar showed lower unipolar voltage (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The hypothesis was that endocardial areas of scar may show low bipolar voltage but near‐normal unipolar voltage. Unipolar voltage maps include the far‐field electrical activity from the overlying viable myocardium and hence can differentiate thin endocardial scars from thick transmural scars 16, 17. In this study, in the three dogs with large confluent infarcts, endocardial scar areas showed high unipolar voltage (>15 mV) and transmural scar showed lower unipolar voltage (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Remarkably, endocardial voltage mapping of the RV and LV can help in evaluating the extent of epicardial abnormalities with a cutoff value of 5.5 mV and 8.3 mV for the RV and LV, respectively 71, 72. Arrhythmogenic potentials or local abnormal ventricular activity potentials can be adjusted objectively through a novel quantification analysis, such as simultaneous amplitude frequency electrogram transformation (SAFE‐T) maps 73.…”
Section: Management Of Vt In Nicmmentioning
confidence: 99%
“…Viability of the interventricular septum (IVS) was defined by averaging the measurements obtained in the septal and basal septal areas. In accordance with previous data on electroanatomical mapping in nonischemic DCM 11, transendocardial delivery of cell suspension was performed with MyoStar injection catheter targeting areas with unipolar voltage ≥8.27 mV and linear shortening <6%. Each patient received 20 injections of 0.3 ml.…”
Section: Methodsmentioning
confidence: 98%